Tackling Challenges and Exploring Opportunities in Cathode Binder Innovation - Lai, Tingrun; Wang, Li; Liu, Zhibei; Bhayo, Adnan Murad; Wang, Yude; He, Xiangming (Nano-Micro Letters, 2025)
Long-life energy storage batteries are integral to energy storage systems and electric vehicles, with lithium-ion batteries (LIBs) currently being the preferred option for extended usage-life energy storage. To further extend the life span of LIBs, it is essential to intensify investments in battery design, manufacturing processes, and the advancement of ancillary materials. The pursuit of long durability introduces new challenges for battery energy density. The advent of electrode material offers effective support in enhancing the battery’s long-duration performance. Often underestimated as part of the cathode composition, the binder plays a pivotal role in the longevity and electrochemical performance of the electrode. Maintaining the mechanical integrity of the electrode through judicious binder design is a fundamental requirement for achieving consistent long-life cycles and high energy density. This paper primarily concentrates on the commonly employed cathode systems in lithium-ion batteries, elucidates the significance of binders for both, discusses the application status, strengths, and weaknesses of novel binders, and ultimately puts forth corresponding optimization strategies. It underscores the critical function of binders in enhancing battery performance and advancing the sustainable development of lithium-ion batteries, aiming to offer fresh insights and perspectives for the design of high-performance LIBs. Highlights: 1 Binders play a crucial role in the lifespan and performance of electrodes, but they are often overlooked. This paper mainly reviews the significance of the role of binders on cathode materials and the optimization strategies. 2 Focusing on LiFePO₄ and transition metal oxide cathode systems, this review systematically summarizes performance optimization strategies for novel binders tailored to the respective advantages and limitations of different cathodes. 3 The future development trend of cathode binders is analyzed, emphasizing the challenges and opportunities faced by binders in thermal safety and all-solid-state systems.